A new species of Trachelopachys Simon, 1897 (Araneae: Trachelidae) from Amazonia - Pantoja, Paulo; Saturnino, Regiane; Bonaldo, Alexandre B. (Zootaxa, 2021)
The genus Trachelopachys Simon, 1897 was erected to accommodate Trachelas sericeus Simon, 1886, a species known from southern South America. Platnick (1975) presented a taxonomic review of the genus and Platnick & Rocha (1995) added a new species and transferred two additional species to the genus, raising the known species diversity of Trachelopachys to 15 species. The genus is distributed in South America, their members are small and colorful, and are distinguished from other trachelines by their darkened carapace, the S-shaped tegular sperm duct and the retrolaterally directed embolus of the male palp (Platnick 1975: fig 12), and the presence of a basal spermathecal lobe in females (Platnick 1975: fig 15). Here we describe the 16th species of the genus, Trachelopachys camarapi sp. nov. (Fig. 1), known from both sexes and recorded in a natural savanna (Fig. 2) at Portel municipality, state of Pará, Brazil.